PERLINDUNGAN ANAK DALAM KONFLIK SOSIAL - Tasya Ramadhani; Dara Manista Harwika (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2021)
All over the world, there are many problems related to children. Children often become victims, both within the internal family or externally such as the environment in which they are located. In addition, the environment can also affect the development of children. This ideal environment guarantees the child's protection for himself. Child protection in Indonesia is manifested in legal materials. The Convention on the Rights of the Child, which contains legal material for child protection, was then ratified into a child protection law, there are also laws on child welfare and laws on human rights. This paper will discuss the impact of social conflict on psychological and physical conditions on children and understand the efforts made to protect children during social conflicts and after social conflicts. The method we use is normative juridical by collecting written rules, literature books, and journals as well as an expert opinion then analyzing this literature and reviews and combining them into a coherent article. The result of this paper is that social conflict has a major impact on the survival and development of children. Therefore, it needs proper protection for children so that children can enjoy their rights humanely.